Gold Ions Recovery by Self-Flocculating Microalga and Fungi-Algae Pellets with Simultaneous Microalgal Bioflocculation - Chirwa, Evans M.N. (University of Pretoria, 2020)
Thesis (PhD (Chemical Engineering))--University of Pretoria, 2020.